Frequency of Hypocalcemia in chronic Liver Disease Patients - Bashir, Amir (Indus Journal of Bioscience Research, 2025)
Introduction: Chronic liver disease (CLD) frequently leads to electrolyte imbalances, including hypocalcemia, due to impaired hepatic function. Hypocalcemia has significant clinical implications, particularly in advanced stages of CLD. Objectives: To determine the frequency of hypocalcemia in chronic liver disease patients. Materials and Methods: This descriptive cross-sectional study was conducted at Shahida Islam Teaching Hospital, Lodhran, Pakistan in the duration from 14 September, 2024 to 12 March, 2025. A total of 81 CLD patients were included using non-probability consecutive sampling. Corrected serum calcium levels were measured, and data were analyzed using SPSS 25.0. Results: Published reports indicate that hypocalcemia was noted in 27 percent of patients in the study, most of whom were in Child-Pugh Class B and C. Higher use was reported by patients with low SEP and those who had had the disease for longer. Gender and BMI did not correlate. Conclusion: It should, however, be noted that hypocalcemia is primarily present in the advanced stages of CLD. Patients’ outcomes may be enhanced when these practices are regularly observed, and early intercessions are made.